Modal evaluation of fluid volume in spacecraft propellant tanks - Crosby, Kevin (Proceedings of the Wisconsin Space Conference, 2014)
A novel, real-time method of determining the volume of propellant present in a spacecraft tank in reduced gravity is presented. In the experiment reported here, modal analysis techniques are applied to detect shifts in resonant mode frequencies of a fluid-loaded tank as fluid is drained from the tank. These experiments are conducted in the weightless environment of parabolic flights through participation in the NASA Systems Engineering Exploration Discovery (SEED) program. Ground testing of the experimental methods is compared with the flight data, and the resolution of the analysis is estimated to be better than 10% of actual fill-fraction. Comparison with existing direct and indirect techniques for assessing propellant volume in reduced gravity suggests that the modal analysis method may prove to be more cost effective and afford better resolution than existing methods.Â 